3D Printing of Cytocompatible Graphene/Alginate Scaffolds for Mimetic Tissue Constructs - Li, Jianfeng; Liu, Xiao; Crook, Jeremy M.; Wallace, Gordon G. (Frontiers in Bioengineering and Biotechnology, 2020)
Tissue engineering, based on a combination of 3D printing, biomaterials blending and stem cell technology, offers the potential to establish customized, transplantable autologous implants using a patient‘s own cells. Graphene, as a two-dimensional (2D) version of carbon, has shown great potential for tissue engineering. Here, we describe a novel combination of graphene with 3D printed alginate (Alg)-based scaffolds for human adipose stem cell (ADSC) support and osteogenic induction. Alg printing was enabled through addition of gelatin (Gel) that was removed after printing, and the 3D structure was then coated with graphene oxide (GO). GO was chemically reduced with a biocompatible reductant (ascorbic acid) to provide electrical conductivity and cell affinity sites. The reduced 3D graphene oxide (RGO)/Alg scaffold has good cytocompatibility and can support human ADSC proliferation and osteogenic differentiation. Our finding supports the potential for the printed scaffold’s use for in vitro engineering of bone and other tissues using ADSCs and potentially other human stem cells, as well as in vivo regenerative medicine.